The Cosmopolitical Dimension: Citizenship, Borders, and Foreignness in E. Balibar - Sainz Pezonaga, Aurelio (Res Publica. Revista de Historia de las Ideas Políticas, 2024)
The link between Balibar's thinking on citizenship and his reflection on borders comes in the intersection between the citizenships of the border and the borders of citizenship. This intersecting structure is sustained by a double aspect of citizenship, as both autonomous and heteronomous, where the contradiction of national citizenship, citizenship that is legally recognized only within the borders of the nation-state, prevails. Balibar's hypothesis is that the contradiction of national citizenship is not a logical contradiction between the universal of citizenship and the particular of the nation, but a historical contradiction in which the symbolic and the institutional are inseparable. The historical response to the historical contradiction advances through the cosmopolitical dimension of politics, where citizenship is not linked to nationality but to foreignness.
Keywords: Frontiers of Citizenship; Citizenship of the Border; Equaliberty; National Citizenship; Civility